2017
DOI: 10.1093/intqhc/mzw160
|View full text |Cite
|
Sign up to set email alerts
|

Consumer satisfaction with tertiary healthcare in China: findings from the 2015 China National Patient Survey

Abstract: Chinese hospitals need to pay more attention to offering more humane care to patients, hospital environment and process management improvement, reducing waiting times for seeing doctors and outpatient testing, and improving amenity services such as better food in the wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 15 publications
5
70
2
Order By: Relevance
“…Our study showed that most of the clients were satisfied with the facility environment (e.g., facility environment, cleanliness) provided by the health scheme which is in a similar line of the findings of other studies where the hospital environment, cleanliness and process management have been recognized as crucial patient satisfaction factors and a better physical environment of a health facility yielded greater patient satisfaction and even led to a positive perception towards the healthcare providers [17,44,45]. However, the literature suggests that the physical environment is able to produce reactions of dissatisfaction level rather than increasing satisfaction level as the environmental contamination is directly linked with the healthcare-associated infection [44,46,47].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our study showed that most of the clients were satisfied with the facility environment (e.g., facility environment, cleanliness) provided by the health scheme which is in a similar line of the findings of other studies where the hospital environment, cleanliness and process management have been recognized as crucial patient satisfaction factors and a better physical environment of a health facility yielded greater patient satisfaction and even led to a positive perception towards the healthcare providers [17,44,45]. However, the literature suggests that the physical environment is able to produce reactions of dissatisfaction level rather than increasing satisfaction level as the environmental contamination is directly linked with the healthcare-associated infection [44,46,47].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the Cronbach’s satisfaction score was 0.92 for all of the satisfaction domains, which was significantly higher than the standard scale value (>0.72), i.e., clients were more satisfied with each of the services [17,23]. Furthermore, it signified that this was a positive indicator of internal consistency within each domain and the acceptable reliability of the satisfaction domains on the services provided by the health scheme.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations